PENGARUH ASIMETRI INFORMASI, UKURAN PERUSAHAAN DAN FINANCIAL LEVERAGE TERHADAP PRAKTEK MANAJEMEN LABA : Perusahaan Manufaktur Sektor Industri Food and Beverages yang terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2016-2018 - Suci Fitriani; Rahmawati Rahmawati (Jurnal Riset Manajemen Indonesia, 2019)
This study aimed to analyze the factors that influence earnings management in companies included in the Indonesia Stock Exchange (BEI). The variables used in the analysis or earnings management practices are information asymmetry, company size and financial leverage. The study was conducted on companies listed on the Indonesian Stock Exchange (BEI) respectively for the period 2016-2018. Engineering samples are used in purposive sampling, in order to obtain as many as 13 sample companies. Testing method of data using multiple linear analysis. Based in the result of the test data, found that simultaneous variable information asymmetry, company size and financial leverages effect on Earning Management. Partially, variable information asymmetry, company size effect on Earning Management, and financial leverage no significant effect on Earnings Management.